Dietary resveratrol improves immunity and antioxidant defense in ewes by regulating the rumen microbiome and metabolome across different reproductive stages - Li, Xiongxiong; Sha, Yuzhu; Li, Shuyan; Wang, Zhengwen; Yang, Yanan; Jiao, Ting; Zhao, Shengguo (Frontiers in Immunology, 2024)
Resveratrol (Res), a natural plant antitoxin polyphenol, is widely used in animal husbandry due to its antioxidant and anti-inflammatory properties, and current research has focused on humans, sows, and female mice. This study aimed to analyze the effects of dietary Res supplementation in ewes on antioxidant activity, immune responses, hormone levels, rumen microbiota and metabolites across various reproductive stages (estrus, pregnancy, and lactation). Twenty-four healthy ewe lambs (Hu sheep, 2 months old) with a similar body weight (BW) (mean: 21.79 ± 2.09 kg) were selected and randomly divided into two groups: the control group (Con) and the Res group (Res). The Res group received 10 mg/kg Res (based on BW) in addition to their basal diet. Res increased the levels of follicle-stimulating hormone (FSH), luteinizing hormone (LH), and estradiol (E2) in ewes at sexual maturity (p < 0.05). Additionally, Res supplementation induced significant increases in serum glutathione peroxidase (GSH-Px) (p =0.031), IgG (p =0.031), FSH, and LH levels during estrus (p < 0.05); serum IgA, IgG and IgM during pregnancy and lactation (p < 0.05); and serum LH, glucose, GSH-Px, and catalase (CAT) levels during lactation (p < 0.05). Meanwhile, serum interleukin 1β (IL-1β) (p =0.005) and cholesterol levels during the lactation stage (p = 0.041) decreased following Res supplementation. Notably, colostrum IgA, IgG, and fat concentrations were significantly higher in the Res group than in the Con group (p < 0.05). Moreover, Res altered the rumen microbiota in ewes. Specifically, the relative abundance of Prevotella (p < 0.05) during pregnancy and Rikenellaceae_RC9_gut_group (p < 0.001) during lactation were significantly increased in ewes under Res treatment. The abundance of Rikenellaceae_RC9_gut_group was positively correlated with the levels of Ig A, Ig M, E2, FSH, LH, GSH-PX, and CAT. Additionally, Res altered the activity of metabolic pathways such as progesterone-mediated oocyte maturation, the estrogen signaling pathway, ovarian steroidogenesis, and the AMPK signaling pathway, and the levels of AICAR and 2-hydroxyestradiol metabolites, both during pregnancy and lactation. There findings show that Res can improve health, antioxidant status, and immune activity throughout the reproductive cycle in ewes by regulating rumen microorganisms and metabolites.